Single Cone Obturation versus Cold Lateral Compaction Techniques with Bioceramic and Resin Sealers: Quality of Obturation and Push-Out Bond Strength - Ahmad Nouroloyouni; Vahid Samadi; Amin Salem Milani; Sara Noorolouny; Haleh Valizadeh-Haghi (International Journal of Dentistry)
Objectives. This study compared the obturation quality and push-out bond strength of single cone obturation (SCO) and cold lateral compaction (CLC) with AH-Plus and Sure Seal Root (SSR). Materials and Methods. This in vitro experimental study was conducted on 88 single-rootedsingle-canal teeth with straight roots that were randomly divided into four groups (n = 22). All teeth were decoronated and underwent cleaning and shaping. Obturation was performed with AH-Plus and SCO technique in group 1 (SAH), AH-Plus and CLC technique in group 2 (LAH), SSR and SCO technique in group 3 (SS), and SSR and CLC technique in group 4 (LS). The roots were then sectioned into 3-mm thick slices and underwent digital photography at x25 magnification to assess the quality of obturation in the coronal, middle, and apical thirds by Image J software. The PBS was measured by a universal testing machine. The mode of failure was also determined under a stereomicroscope. Results. The PBS was significantly higher in the LSS group than LAH and SAH groups, and also in the SSS group than the SAH group in all sections. The PBS in the LSS group was significantly higher than SSS in the coronal and middle thirds. Voids were significantly lower in LAH than in the SAH group in all sections. In LSS, voids in the coronal third were significantly lower than in LAH. In the middle third, voids in SSS were significantly lower than in SAH. The groups had no significant difference in the mode of failure (P > 0.05). The mean percentage of gutta-percha in the use of AH-Plus sealer was significantly higher than SSR (P < 0.05). The mean percentage of gutta-percha in the coronal third was lower than that in the middle and apical thirds (P < 0.05). Conclusion. SSR showed higher PBS and less voids than AH-Plus. High PBS of the CLC/SSR group showed that CLC should still be preferred to SCO, and in the case of using SCO, SSR should be preferred to AH-Plus.